Relações familiares e institucionais de jovens que cumpriram medida socioeducativa em meio aberto - Costa, Lizinara Pereira da (2016)
This current study aims to discuss the issue of adolescents in conflict with the law and the socio-educational measures (MSE) in assisted freedom. This work was divided into two articles, one theoretical and one empirical. The first is a review of literature on the subject teenager in conflict with the law: a review of the contributions of social, family and individual variables. In addition to the macro social conditions, the problem of the offender s behavior suffers the influence of control institutions (family, school), peer groups and individual aspects (biological and personality characteristics). To understand and address the juvenile delinquency, it becomes important to consider many aspects from a broader view in order to assess the conditions of a society at the structural level up to a vision that incorporates aspects of micro-social contexts of socio-psychological and individual levels. The second article explored the opinion of three teenagers on the MSE compliance experience in liberty. The qualitative analysis showed the following sub-units and categories: influence of family relations (conflict and/or emotional distancing, emotional support and instrumental); influence of institutional relations (emotional and instrumental support); and future plans (study, work and family). The results showed that both the relations with family and the relations with friendships seem to have contributed to these young people to engage in illegal acts. In conclusion, it is believed not to be feasible any intervention to adolescents in conflict with the law without covering the family with the same emphasis. It is highlighted the importance of studies that investigate individual biological factors along with external, family and cultural factors, so they can have subsidies targeted the prevention and the intervention in these situations.